LAND ASSET APPRAISAL POST-TAX AMNESTY, AN ADVANTAGE FOR TAXPAYER - Aniek Juliarini (JAFFA, 2017)
Post tax amnesty 2016, the taxpayer who does not comply tax amnesty, or taxprayer who does not properly report the entire asset, the concerned asset is considered as received or obtained income when the data and/or information is discovered on the asset. According to Circular Letter of the Directorate General of Taxes Number SE-24/PJ/2017, appraisal of non-cash asset shall be conducted in accordance with the asset state and condition as of December 31, 2015 (or at the end of a different period for a Taxpayer who have a different book year ending). For the land asset, the value is set using Land Building Tax Imposition Base (NJOP-PBB). This study proves that Tax Imposition Base (NJOP) is below the market price. The descriptive qualitative method was applied in analyzing whether or not the provisions as regulated in Circular Letter of the Directorate General of Taxes Number SE-24/PJ/2017 is proper. This study concludes that Taxpayer will gain two advantages from the enactment of Circular Letter of the Directorate General of Tax Number SE-24/PJ/2017 that is 1). Land asset value is based on Land Building Tax Imposition Base; 2). Land Building Tax Imposition Base used is 2015 Land Building Tax Imposition Base, instead of the applicable Land Building Tax Imposition Base when the asset is discovered.